The “Academic-Market Hybrid” Model: Unblocking the Bottlenecks in Patent Commercialization at Higher Education Institutions - Van Hai, Tran (VNU Journal of Science: Policy and Management Studies; Vol 42 No 1DO - 10.25073/2588-1116/vnupam.4616, 2026)
Abstract: In recent years, the number of patents owned by higher education institutions has increased significantly; however, the proportion of patents that are successfully commercialized remains very low. Many universities prioritize R&D activities aimed at improving institutional rankings, and in numerous cases, patent applications are filed primarily to attract academic recognition rather than to pursue commercialization. This article analyzes the principal bottleneck hindering patent commercialization in Vietnamese higher education institution, which is the gap between research outputs and market demand. It further proposes the development of an “academic–market hybrid” model as a solution to remove this bottleneck and enhance the commercialization of patents within higher education institutions. Keywords: Higher Education Institution; Patent Commercialization; Academic – Market Hybrid.